Coxsackievirus B3-associated panuveitis. Issue 3 (March 1993) - Förster, W; Bialasiewicz, A A; Busse, H
Abstract : A 29-year-old woman suffered from headaches, diarrhoea, and high grade fever followed by a unilateral retinal vasculitis, papillitis, and chorioretinitis. Abnormal electrocardiographic findings and antibody titre dynamics strongly suggested a coxsackievirus B3 infection. With respect to prior observations on coxsackievirus B group associated uveitis this viral infection may be considered in patients with well defined extraocular manifestations and uveitis.